The Effectiveness of the Marmet Technique to Increase Breast Milk Production in Breastfeeding Mothers at the Tateli Community Health Center, Minahasa Regency - Pasambo, Yourisna; Tumanken, Greischa Audrey; Tamunu, Esther; Ponidjan, Tati S.; Sarimin, Dorce Sisfiani; Kanine, Esrom (Jurnal Ilmiah Perawat Manado (Juiperdo), 2024)
Introduction: Newborn babies must receive the best care, including food, where breast milk is the best intake to meet the baby's nutritional needs. In 2021, exclusive breastfeeding coverage in North Sulawesi Province will be 30.2%, lower than the national target of 80%. Several factors influence a mother's failure to provide exclusive breastfeeding, including psychological factors, maternal age, maternal occupation, maternal knowledge, family support, and lack of oxytocin and prolactin reflexes which can be influenced by lack of physical preparation (such as breasts) when breastfeeding. One of the things that health workers can do in this case is to help increase breast milk production, one of which is through the marmet technique. The marmet technique is a combination of expressing breast milk and massaging the breasts to optimize the breast milk reflex. This research is objective to evaluate the effectiveness of the marmet technique in increasing breast milk production in mothers breastfeeding babies aged 0-6 months at the Tateli Community Health Center, Minahasa Regency. Method: Research design using Almost Experiment with 30 breastfeeding mothers as samples, selected through purposive sampling. Results showed a significant increase in breast milk production after the intervention (p-Value < 0.05). Concluded that the marmet technique is effective in increasing breast milk production in mothers breastfeeding babies 0-6 months, and it is recommended that health practitioners introduce and train the marmet technique to breastfeeding mothers as part of efforts to increase breast milk production.